2012
DOI: 10.1021/ie200870m
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design and Decision for Combined Steam Reforming Process with Dry Methane Reforming to Reuse CO2 as a Raw Material

Abstract: Carbon dioxide (CO 2 ) conversion technology has been estimated as a potentially practical solution for global warming problems although it still has some weaknesses such as cost and energy consumption. In this study, a combined steam reforming process with dry methane reforming process for the CO 2 treatment was investigated. Because the dry methane reforming process could generate synthesis gas from carbon dioxide, it could decrease the CO 2 emissions from the existing steam reforming process. Models for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…In addition, it has been reported that the dry reforming reaction is favourable at high temperature [21][22][23].…”
Section: Effect Of Catalyst Preparation Methodsmentioning
confidence: 99%
“…In addition, it has been reported that the dry reforming reaction is favourable at high temperature [21][22][23].…”
Section: Effect Of Catalyst Preparation Methodsmentioning
confidence: 99%
“…Climate change due to increasing concentrations of global warming gases, particularly CO 2 and CH 4 in the atmosphere is a great concern globally. 1,2 Most of the CO 2 released into the atmosphere is due to burning of fossil fuels like coal, natural gas and oil. The amount of carbon dioxide reaching the atmosphere can be minimized by different techniques such as; CO 2 capture, transportation and sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…In the process, hydrogen was produced as the salable product and is worth 1.5–1.8 $ kWh −1 26. The separation cost was estimated to be 56 $ $ t_{{{\rm{H}}_2}}^{ - 1} $ 4. The compression cost for captured CO 2 is the sum of the electricity and cooling water costs which was estimated to be 10.5 $ t −1 of compressed CO 2 27, 28.…”
Section: Methodsmentioning
confidence: 99%
“…Syngas is an intermediate used to generate various products such as methanol, dimethyl ether (DME), and long‐chain, i.e., C10–C16 alcohols 3. The main reaction that produces syngas is the steam methane reforming (SMR) process 4, 5, which requires much energy to produce an ideal H 2 /CO ratio (H 2 :CO = 1.0–2.0). For every kg H 2 production, ∼ 134 MJ energy is consumed.…”
Section: Introductionmentioning
confidence: 99%